Factors Influencing the Information and Communication Technology (ICT) of Third Party Logistics in Malaysia - Awoyemi Adebare Omotayo; Mustakim Melan (International Journal of Supply Chain Management, 2017)
AbstractThe function of Information Communication Technology is still unevenly distributed among the logistics providers leading to sizeable front-liners controlling the logistics market. The ICT involves directly with the customer relationships, manufacturing, transportation, warehousing networks and data streams. This study targeted at providing remedies to the most of existing gaps relating the influence of ICT facilities in logistics industry especially among the 3PLs in Malaysia. Third Party Logistics Services can be referred as an outsourcing of transport and logistics activities belong to other companies in the movement of goods to meet their purpose. In most cases, more than one activity is outsourced and it includes storage, warehousing and transportation. The study utilized in the used of questionnaire to gather the required information from Third party logistics service providers. The data were analysed among 150 respondents and the correlated result shows that the selection of an appropriate tool of ICT has a significant impact on the competitive advantage of third party logistics companies. The result of the study is able to be used for the measurement of the performance and benchmarking on the importance of ICT in leading the 3PLs logistics industry in future. KeywordsInformation, communication, technology, third party Logistics, transportation, competitive advantage